Exploring the roots of digital and media literacy through personal narrative - Hobbs, Renee (Philadelphia, Pennsylvania : Temple University Press, 2016)
"Exploring the Roots of Digital and Media Literacy through Personal Narrative provides a wide-ranging look at the origins, concepts, theories, and practices of the field. This unique, exciting collection of essays by a range of distinguished scholars and practitioners offers insights into the scholars and thinkers who fertilized the minds of those who helped shape the theory and practice of digital and media literacy education. Each chapter describes an individual whom the author considers to be a type of "grandparent." By weaving together two sets of personal stories--that of the contributing author and that of the key ideas and life history of the historical figure under their scrutiny--major concepts of digital media and learning emerge. "--
Machine generated contents note: Contents: Introduction and the Landscape Historical Roots of Media Literacy David Weinberger on Martin Heidegger Lance Strate on Marshall McLuhan Dana Polan on Roland Barthes Cynthia Lewis on Mikhail Bakhtin Srividya Ramasubramanian on Gordon Allport Michael Robb Grieco on Michael Foucault Gianna Cappello on Theodor Adorno Douglas Kellner on Herbert Marcuse Henry Jenkins on John Fiske Amy Petersen Jensen on Bertolt Brecht Donna Alvermann on Simone de Beauvoir Jeremiah Dyehouse on John Dewey Renee Hobbs on Jerome Bruner Vanessa Domine on Neil Postman Peter Gutierrez on Scott McCloud Susan Moeller on Roland Barthes.
Includes bibliographical references and index.
Keywords: Media literacy; Digital media; Mass media -- Philosophy; Digital media -- Philosophy; Mass media and culture; Mass media in education; Scholars -- Biography; Intellectuals -- Biography; SOCIAL SCIENCE / Media Studies; EDUCATION / Computers & Technology